TJS 2015
DOI: 10.15547/tjs.2015.s.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of destination management and marketing organizations in regional development

Abstract: In recent years Destination Management and Marketing Organization (DMMOs) became a mainstream factor in identifying successful development of a destination and its perspectives for better position in highly competitive tourism markets. They are not only representing a specific destination but are also striving to community development that bring long-term benefits such as attracting more visitors, increasing the economic gains, facilitating future marketing and product development decisions, and generally cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…The finding was established after obtaining a standardized beta value of 0.58 and a significant p-value of 0.00 which supported the initial H 1 that destinations management has a significant effect on the sustainability of hospitality industry. Aligning with this finding Timareva et al (2015) indicated that destination management enhances tourism development and impact on the performance of hospitality firm. Similarly, Iwara et al (2017) indicated that effective destination management improved the provision of modern facilities, accommodations, amenities, enhanced security and continuous improvement of services offered in destinations, thereby providing memorable tourist and visitors experience as well as increasing tourist/visitors influx in the destinations which results in increased revenue generation as well as sustainability of the hospitality industry.…”
Section: Hypothesessupporting
confidence: 70%
See 2 more Smart Citations
“…The finding was established after obtaining a standardized beta value of 0.58 and a significant p-value of 0.00 which supported the initial H 1 that destinations management has a significant effect on the sustainability of hospitality industry. Aligning with this finding Timareva et al (2015) indicated that destination management enhances tourism development and impact on the performance of hospitality firm. Similarly, Iwara et al (2017) indicated that effective destination management improved the provision of modern facilities, accommodations, amenities, enhanced security and continuous improvement of services offered in destinations, thereby providing memorable tourist and visitors experience as well as increasing tourist/visitors influx in the destinations which results in increased revenue generation as well as sustainability of the hospitality industry.…”
Section: Hypothesessupporting
confidence: 70%
“…Effective destination management enhances the development of the destinations, tourism supply, facilities/infrastructure, improved services and attract repeat visit by tourist and visitors to the destinations (Zemla, 2016;Chia et al, 2021). Study by Timareva et al (2015) indicated that destination management enhances tourism development and impacts on the performance of hospitality firm.…”
Section: Destinations Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A good image of infrastructure can be one of the tourist attractions (Brown, Chalip, Jago, & Mules, 2004;Kim & Chalip, 2004). Ritchie and Smith (1991) (Timareva et al, 2015). It can be concluded that tourism facilities are the convenience of visitors to enjoy, feel the comfort that has been provided by e-ISSN: 2407-392X.…”
Section: Sport Tourismmentioning
confidence: 99%
“…Methodologies such as key performance indicators are also important strategic tools for destination management and marketing organizations (DMMOs) that manage destinations and express interest in their member hotels. As for the DMMOs, they have developed a positive attitude towards tourism activities, recognizing their contribution to economic and social growth [3]. Unsurprisingly, growth is not limited exclusively in the larger regions, as natural and cultural resources are abundant all over the nation [1].…”
Section: Introductionmentioning
confidence: 99%